Faster, higher, stronger, older: Relative age effects are most influential during the youngest age grade of track and field athletics in the United Kingdom - Kearney, P. E.; Hayes, P. R.; Nevill, A. (Journal of Sports Sciences, 2019)
The relative age effect (RAE) is a common phenomenon in youth sport, whereby children born early in the selection year are more likely to experience success and to sustain participation. There is a lack of research investigating variables which influence RAEs within track and field athletics. Such information is vital to guide policies in relation to competition structure, youth development squads and coach education. A database of competition results was analysed to determine the extent to which RAEs were present in track and field athletics in the United Kingdom. Subsequent analyses examined whether age, sex, event and skill level influenced the RAE. Examination of 77,571 records revealed that RAEs were widespread, but most pronounced during Under 13 (U13) competitions; that is, during athletes` first exposure to formal track and field competition. Sex, event and skill level further influenced the existence and magnitude of RAEs at different age grades. Relative age is a key influencing factor within track and field athletics, especially at the youngest age category. Consequently, national governing bodies need to consider what administrative and stakeholder initiatives are necessary to minimise the effects of RAEs on young athletes` early experiences of competition.